FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PERAWAT DALAM PENERAPAN UNIVERSAL PRECAUTIONS DI RSUP Prof. Dr. R. D. KANDOU MANADO - Lorrien G. Runtu; Fitri Haryanti; T. Baning Rahayujati (Jurnal Ilmiah Perawat Manado (Juiperdo), 2013)
Nosocomial infections (INOS) is a major problem in every hospital . Research conducted by WHO showed that prevalence ranges from 8.7 % INOS of 55 hospitals in 14 countries from Europe , the Middle East , Southeast Asia and the Pacific still showed the presence of nosocomial infection in Southeast Asia was 10 % ( Harry , 2006). By Prof. RS profile. Dr. . R. D. Kandou In 2010 the ratio of patients hospitalized with nurses 1.3 , this shows that the workload of nurses is quite steeper attributed to the data BOR 85 % . In 2009-2010 there were 77 complaints were addressed through the mass media relating to the service in the hospital, the last 2 years has not been routinely reported incidence INOS and in 2005 was accredited hospital but 3 activity has not escaped, the K3 services, and service PERISTI INOS. Research Objectives. determine the relationship between nurse characteristics (age, education, training, long work) with the application of universal precautions, the relationship between perception of completeness of the application infrastructure with Universa precautions , the relationship between the perception of nurses regarding nosocomial infection with the application of universal precautions. This study is an observational research, using cross-sectional design . The research was conducted in the department of Prof . Dr. R.D. Kandou Manado. The number of samples in this study were 100 people perawat.Waktu study in December 2011 to February 2012. This study measuring instrument is structured questionnaires and observation sheets. How to purposive sampling , data were analyzed using chi-square and logistic regression. Results of data analysis showed that education related to the behavior of nurses in the application ofuniversal precautions. Age , length of work and training unrelated to the behavior of nurses in theapplication of universal precautions. Infrastructure completeness perception, the perception of themagnitude of the problem of nosocomial infections, nosocomial infection risk perception and selfperceptionabilities nurses prevent nosocomial infection associated with the behavior of nurses in theapplication of universal precautions. Conclusion. Individual characteristics not related to theapplication, universal precautions. Infrastructure completeness perception, and the perception ofself-efficacy related to behavioral nurse nurses in the application of universal precautions